Epidemiological Studies on Dermatophytoses in Warangal District, Telangana State, India (Global Journal of Medical Research, 2015)
The frequency of superficial fungal infections is more in hot and humid climate. Seasonal variation of skin diseases, a subject of much epidemiological interest, has been studied for centuries. The present study report is on dermatophytoses in different clinical conditions such as age, sex and seasonal impact in Warangal District, A.P. A retrospective study was done on all new outpatients visiting a single dermatologist Dr. Ramesh, at the Ramesh skin hospital, Warangal, Andhra Pradesh. The study population comprised of all new subjects visiting the outpatient department, from January to December, from 2008-2010. The total number of cases was recorded according to the month wise prevalence.
Keywords: dermatophytosis; tinea or ringworm infections; dermatophytes; woods lamp and skin scrapings